From Bed to Bench and Back: TNF-α, IL-23/IL-17A, and JAK-Dependent Inflammation in the Pathogenesis of Psoriatic Synovitis - Silvagni, Ettore; Missiroli, Sonia; Perrone, Mariasole; Patergnani, Simone; Boncompagni, Caterina; Bortoluzzi, Alessandra; Govoni, Marcello; Giorgi, Carlotta; Alivernini, Stefano; Pinton, Paolo; Scirè, Carlo Alberto (Frontiers in Pharmacology, 2021)
Psoriatic arthritis (PsA) is a chronic inflammatory immune-mediated disease with a burdensome impact on quality of life and substantial healthcare costs. To date, pharmacological interventions with different mechanisms of action, including conventional synthetic (cs), biological (b), and targeted synthetic (ts) disease-modifying antirheumatic drugs (DMARDs), have been proven efficacious, despite a relevant proportion of failures. The current approach in clinical practice and research is typically ‘predictive’: the expected response is based on stratification according to clinical, imaging and laboratory data, with a ‘heuristic’ approach based on ‘trial and error’. Several available therapeutic options target the TNF-α pathway, while others are directed against the IL-23/IL-17A axis. Janus Kinase inhibitors (JAKis), instead, simultaneously block different pathways, endowing these drugs with a potentially ‘broad-spectrum’ mechanism of action. It is not clear, however, whether targeting a specific pathway (e.g., TNF-α or the IL-23/IL-17 axis) could result in discordant effects over other approaches. In particular, in the case of ‘refractory to a treatment’ patients, other pathways might be hyperactivated, with opposing, synergistic or redundant biological significance. On the other hand, refractory states could be purely resistant to treatment as a whole. Since chronic synovitis is one of the primary targets of inflammation in PsA, synovial biomarkers could be useful in depicting specific biological characteristics of the inflammatory burden at the single-patient level, and despite not yet being implemented in clinical practice, these biomarkers might help in selecting the proper treatment. In this narrative review, we will provide an up-to-date overview of the knowledge in the field of psoriatic synovitis with regard to studies investigating the relationships among different activated proinflammatory processes suitable for targeting by different available drugs. The final objective is to clarify the state of the art in the field of personalized medicine for psoriatic disease, aiming at moving beyond the current treatment schedules towards a patient-centered approach.